Valente y lo incomprensible. Fragmentos de una lectura a tientas (TEST Ticontre. Theory Text Translation, 2020)
AbstractAs a tribute to the poet, we propose a primordial reading about the Valente`spoetry to do an exercise of approximation to   understand  the poem having onlythe materials offered by the poet. In this case we will dispense with a traditionalcritical support and our references will just be his own bibliography.